KONSEP KAFA’AH MASYARAKAT SUMBERBENDO PERSPEKTIF MADZAB SYAFI’I - Ulin Ismatin Nikmah; Arianto (Institut Agama Islam Hasanuddin Pare, 2023)
ABSTRACT This study discusses the concept of kafa'ah from the Sumberbendo community's perspective and its relevance to Islamic law. In accordance with the theory that the author took from the agreement of the madzab scholars about the concept of kafa'ah, namely in terms of religion, wealth, lineage (descendants), profession or work, independence, and not being disabled. The formulation of the problem in this study is how the concept of kafa'ah is from the Sumberbendo community's perspective and its relevance to Islamic law. The purpose of this study is to describe the perspective of the concept of kafa'ah with life and harmony in the household in Sumberbendo Village and to explain the relevance of the concept of kafa'ah with household harmony to Islamic law. As for the results of the study, it was found that the concept of kafa’ah is harmony between husband and wife with the aim of reducing problems that arise. The majority of the people of Sumberbendo only one or two concepts. Although of kafa’ah as a whole, namely focusing on the criteria of religion and or wealth, the community is able to adapt to social differences between couples. And its relevance to islamic law is that although Islam has properly regulated the concept of kafa’ah or equivalence, in it is not fully guided by Islamic provisions. This study uses field research with collection, interview sessions, and documentation. The method uses is a qualitative descriptive method thah describes systematically, actual, and accurately the carefully on documents with the aim of being able to assist in strengthening the analysis. Keywords : kafa'ah, relevance, husband and wife